2016
DOI: 10.1111/codi.13119
|View full text |Cite
|
Sign up to set email alerts
|

Perineal body anatomy seen by three‐dimensional endovaginal ultrasound of asymptomatic nulliparae

Abstract: The PB is divided into two levels with different anatomical relationships with the pelvic floor muscles. 3D-EVUS yields reproducible assessment of this complex structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
(147 reference statements)
0
27
0
Order By: Relevance
“…This method of scanning the perineal body gives the clearest images observed so far in the literature. Previous studies had shown poor repeatability [10,11]. This may be because, in those studies, the perineal body was measured on images that acquired the entire pelvic floor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This method of scanning the perineal body gives the clearest images observed so far in the literature. Previous studies had shown poor repeatability [10,11]. This may be because, in those studies, the perineal body was measured on images that acquired the entire pelvic floor.…”
Section: Discussionmentioning
confidence: 98%
“…In 2016, the perineal body of nulliparous cadavers was visualised using a three-dimensional endovaginal ultrasound ((3D-EVUS) BK high frequency ultrasound scanner, with 3D Viewer offline analysis [11]. In the EVUS scan, the perineal body is visualised as an ovoid structure.…”
Section: Introductionmentioning
confidence: 99%
“…Three‐Dimensional EVUS Once the transducer is advanced to visualize the anterior compartment as in Figure , the 3D volume is obtained. The scan starts from the vesicourethral junction and will continue 6 cm caudal to include the perineal body . The 3D volume is useful for visualization of the levator ani muscle subdivisions and defects, vaginal masses and cysts, slings, and mesh (Figure ) .…”
Section: Specifications Of the Examinationmentioning
confidence: 99%
“…Axial images of the pelvis with high frequency 3D EVUS (9-16 MHz) are similar to those with 3D TPUS, however, the higher frequency provides better resolution of the examined structures [24]. High resolution 3D EVUS allows an accurate evaluation of the symmetry between urethra and the anal canal, the morphology of the urethra (rhabdosphincter, lisosphincter) and of the supporting ligaments and fascia [25], the levator ani muscle subdivisions [26], the indices of levator hiatus (area, length and width) 27], the integrity of the perineal body and the rectovaginal fascia [28], the post-operative evaluation of tapes and meshes to identify displacement, shrinkage, fluid collections, abscesses or hematomas (Figs. 2-3).…”
mentioning
confidence: 99%